DFT-Based Mechanistic Study and QSAR Modeling of Antioxidant Activity of Triazole Derivatives - Imelda; Anggi Febrianti; Aulia Syifa (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Triazole-derived compounds are known to exhibit a variety of favourable biological activities, including antioxidant, anti-inflammatory, and antibacterial activities. Research on the potential of these compounds as antioxidant compounds was carried out theoretically through analysis of global reactivity parameters and measurement of antioxidant activity. The Density Functional Theory (DFT) method was used to study the molecular structure, global reactivity parameters, and hydrogen-atom release mechanism by calculating BDE, IP, PDE, PA, and ETE values. Antioxidant activity was expressed as the Inhibition Concentration 50% (IC50) values obtained from multilinear regression-based Quantitative Structure-Activity Relationship (QSAR) analysis. Validation was performed by comparing theoretical IC50 values with experimental values. The results show that molecule A is the most reactive, followed by molecules B, D, and C, which have the same theoretical IC50 value as the experiment. The interaction of the compounds with ROS and RNS radicals exhibited spontaneous reactions with negative ?G, reinforcing their potential antioxidant activity. This study confirmed that triazole-derived compounds have the potential to be further developed as effective antioxidants.Contribution to Sustainable Development Goals (SDGs): SDG 2 – Zero HungerSDG 3 – Good Health and Well-BeingSDG 12 – Responsible Consumption and Production